(untitled) (Experimental biology, 2016)
Virtually no methods for the determination of molybdenum in the field (test methods), simple and does not require special equipment and specific conditions suitable for the needs of ecologists, medical personnal, biologists, and in connection with the methods for the determination of molybdenum in the environment and biological materials are constantly being improved. Therefore, we have developed a new rapid method for the determination of molybdenum xanthine oxidase. Study on nitrate reductase (NaR) and nitrite reductase (NiR) activities of molybdenum containing enzyme xanthine oxidase (XO) showed that in milk of goat, camel and mare XO exists in molybdenum free form and is inactive. XO is activated by heat treatment of milk at 85oC in 10 min in the presence of exogenous molybdate (Mo) and thiols. Heat treatment without thiol reagents led to the decrease of these activities. It is generally known that XO belongs to thermostable enzymes – XO isolated from liver does not loss activity at 75-80oC temperature in several minutes. Mo atoms bind to sulfhydrile (SH) groups of molybdenum cofactor in the active center of XO. However, denaturation of XO by heat treatment leads to the oxidation of these SH-groups by oxygen. Therefore, in order to defense of these groups of the cofactor during heat treatment of milk different antioxidants were used. One assay was used to determine nitrate reducing (NaR) as well as nitrite reducing (NiR) activities of milk XO: (1) nitrite formation from nitrate by NaR, and (2) nitrite utilization by NiR. For quantitative determination of nitrite sulfanilamide and N-(1-naphtyl)-ethylenediamine were used. Heat treatment of milk in the presence of tungstate resulted in total inhibition of all associated activities of milk XO. It is well known that in the absence of molybdenum its chemical analog tungsten easily replaces the molybdenum in the active center of molybdoenzymes. However, tungsten-enzymes become inactive. These results show that nitrate and nitrite are clearly meant to interact with Mo center of XO of milk. These results convincingly show that in milk prevailing amount of XO molecules do not contain molybdenum. We found that in the presence of phosphate, antioxidants dithiothreitol (DTT), ascorbate (AA) and dithionite (DTN) exogenous Mo forms blue color by sulfanilamide (maximum absorption of the color was 695 nm). When cysteine or glutathione were used as an antioxidants molybdenum was not colored by sulfanilamide, i.e. they did not interfering nitrite determination. Using DTT, phosphate and sulfanilamide it was shown the incorporation of exogenous molybdenum in XO molecule which located in fat globules of milk cream. Thus, the method for molybdenum determination in biological materials represents fast (few minutes), cheap (three not expensive reagents) and harmless (sulfanilamide is antibiotic) procedure. Although the sensitivity of our method as compared with some other methods is lower, it is easy to concentrate of biological materials before molybdenum determination.